Analisis Karakteristik Anak Berkebutuhan Khusus (Autisme) pada Siswa SD Negeri Sudimara Timur 2 Kota Tangerang - Nurfadillah, Septy; Shadiqa, Citra Dzakkiyah; Hasri, Thalia Nindy; Amanda, Mega; Syafitri, Hanna Azhar; Tantular, Lisa Damayanti (TSAQOFAH, 2022)
This research was conducted at SD Negeri Sudimara Timur 2 Tangerang City with the aim of knowing how the characteristics of children with special needs autism and identifying how the implementation of learning, curriculum implementation used in inclusive education at SD Negeri Sudimara Timur 2 Tangerang City was. The method used in this research is using descriptive qualitative research through interviews, observation and documentation. Autism Spectrum Disorder (ADS) is a neurodevelopmental disorder, it affects language development and the child's ability to communicate, interact, and also the child's behavior. Children who are classified as autistic also have other characteristics such as doing repetitive activities and stereotyped movements, rejection of the environment and often giving inappropriate responses to sensory experiences. The results of this study indicate that SD Negeri Sudimara Timur 2 Tangerang City has provided services in the form of inclusive education which has been running for almost a year. The curriculum used follows the National Education Curriculum (K13) which is adjusted to the abilities of each student with special needs.